Implementation of Association Rules to Manage Cross-Selling and Up-Selling for IT Shop - I Wayan Andis Indrawan; Komang Oka Saputra; Linawati Linawati (International Journal of Engineering and Emerging Technology, 2019)
Nowadays sales marketing strategies in showrooms are increasingly innovative. Utilizing information technology, especially data mining to obtain customer habits in shopping. Customer's shopping habits are recorded in each transaction and stored in a data warehouse. This transaction data is actually very valuable and can be elaborated to be used to manage cross selling and up selling in sales stores, including IT showroom stores. IT Showroom stores usually have unusual or unexpected customers shopping for IT needs. Therefore this potential can be exploited for analysis to get behavior from customers by analyzing transactions in a certain period of time using the Rapidminer application. Rapidminer is a fit application to solve this problem because it is equipped with various algorithms, one of which is association rules. Association rules are algorithms that can be used to analyze data and produce recommendations for cross selling and up selling.